Stereotactic Radiosurgery for pituitary adenomas: A review of literature - Kaynat Siddiqui; Saqib Kamran Bakhshi; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2022)
Stereotactic radiosurgery (SRS) is a choice of treatment for pituitary adenomas (PA), particularly for residual or recurrent disease, apart from surgery. It has a progression free survival and endocrine remission rate comparable to surgery, with fewer side effects, making it an ideal tool for dealing with PA. In this review, we have discussed the role of SRS for primary as well as post-operative residual/ recurrent PA, and have assessed its safety and outcomes. Keywords: Pituitary adenoma, Stereotactic Radiosurgery, SRS, Gamma Knife Radiosurgery.